2015 IEEE Conference on Computer Vision and Pattern Recognition (CVPR) 2015
DOI: 10.1109/cvpr.2015.7298842
|View full text |Cite
|
Sign up to set email alerts
|

R6P - Rolling shutter absolute pose problem

Abstract: We present a minimal, non-iterative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 23 publications
1
71
0
Order By: Relevance
“…In [15], a large-scale bundle adjustment with a generalized camera model is proposed and applied to 3D reconstructions from images collected with a rig of RS cameras. Several works [1,22,17] were introduced to solve the absolute pose estimation problem using RS cameras. All these efforts demonstrated the potential of applying 3D algorithms to RS cameras.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [15], a large-scale bundle adjustment with a generalized camera model is proposed and applied to 3D reconstructions from images collected with a rig of RS cameras. Several works [1,22,17] were introduced to solve the absolute pose estimation problem using RS cameras. All these efforts demonstrated the potential of applying 3D algorithms to RS cameras.…”
Section: Related Workmentioning
confidence: 99%
“…Due to the price advantage of the RS camera, many researchers began to propose 3D computer vision algorithms that aim to mitigate the RS effect over the recent years. Although several works have successfully demonstrated stereo [21], sparse and dense 3D reconstruction [15,23] and absolute pose estimation [1,22,17] using RS images, most of these works completely bypassed the initial relative pose estimation, e.g. by substituting it with GPS/INS readings.…”
Section: Introductionmentioning
confidence: 99%
“…They first establish correspondences between pixels in a test image and 3D points in the scene. These 2D-3D matches are then used to estimate the camera pose by applying an npoint-pose (PnP) solver [2,[31][32][33][34] inside a RANSAC [18,22,36,54] loop. Traditionally, the first stage is based on matching descriptors extracted in the test image against descriptors associated with the 3D points.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed R6P is based on the constant linear and angular velocity model as in [14,16,1] but it uses the first order approximation to both the camera orientation and angular velocity, and, therefore, it requires an initialization of the camera orientation, e.g., from P3P [7]. Paper [18] has shown that R6P solver significantly outperforms perspective P3P solver in terms of camera pose precision and the number of inliers captured in the RANSAC loop.…”
Section: Introductionmentioning
confidence: 99%